Hidden in the Desert - Discover Where Nature's Creatures are Hiding - Taylor, Barbara 1954- (Mankato, Minn. : QEB Pub., 2011)
"Gives examples of how animals of North American and African deserts use camouflage to help them adapt to their habitats and hide from predators"--Provided by publisher.
Includes bibliographical references (p. 24) and index.
Keywords: Desert animals -- Juvenile literature. -- Adaptation; Camouflage (Biology) -- Juvenile literature